Cannabis Use, Psychotic Like Experiences and Aberrant Salience in a Sample of Belgian Students. Issue 7 (July 2018) - Bernardini, Francesco; Gobbicchi, Chiara; Attademo, Luigi; Puchalski, Severin; Trezzi, Riccardo; Moretti, Patrizia; Tortorella, Alfonso; Loas, Gwenolé
Abstract : Abstract: The main goal of our study was to investigate the association between psychotic-like experiences, aberrant salience, and cannabis use in a nonclinical sample of Belgian students. The participants were asked to complete a self-report questionnaire on cannabis use. The Community Assessment of Psychic Experiences and the Aberrant Salience Inventory were used to assess psychotic-like experiences and aberrant salience. The final sample was of 257 students. Cannabis users showed significantly higher Aberrant Salience Inventory score and, concerning the Community Assessment of Psychic Experiences, higher total, positive, and negative dimension scores. Years of cannabis use and frequency of use showed a positive correlation with Aberrant Salience Inventory score. Our results support the evidence that cannabis use is associated with an increased rate of psychotic experiences in individuals without a clinical form of psychosis. Future studies are required to better investigate the meaning of the association between cannabis use, psychotic-like experiences, and aberrant salience.